INVESTIGATING BREAKING LOAD AND FATIGUE LIFE OF NUT ELEVATOR CONVEYOR CHAINS IN EAST OIL MILL - Husna Qadirah Binti Zulhas, Nur
In the East Oil Mill, there are several vertical conveyor system, where one of them is TRP-A8H conveyor. In this conveyor system, design conditions including the minimum breaking load and safety factor are vital. Additionally, it is also necessary to analyze fatigue failures due to interference fit in chain assemblies by evaluating contact stress of pin-hole and bushing-hole joints interfaces, where fatigue failure of chain components is determined via Soderberg diagrams. The influence of interference fit to chain fatigue strength, as well as fretting failure are also required to be analyzed. Using analytical method, the minimum breaking load is obtained at 4.48 kN with safety factor of 43.79, which is considered as too large. The von-Mises contact stress that is calculated using Lame’s equation yielded with disparities of ±10% when compared with numerical method. Fatigue strength of the chain components are evaluated by applying maximum and minimum loads as inputs in the numerical simulations, followed by plotting obtained mean and alternating stresses in the Soderberg diagram. Fit with zero interference is compared with interference fit to shows the influence of interference fit. Results attained show that interference fit helped in reducing alternating and mean stress, which elongates the fatigue life of chain. Fretting failure is evaluated from the status of contact surface and compared with past researches. Results show that as the load is increased, contact surface that was initially come into contact became non-contacted, which aid in shorten fatigue life of chain.